Incidence of candidemia and prevalence of azole-resistant candidemia at a tertiary South African hospital – A retrospective laboratory analysis 2016–2020 - Vindana Chibabhai (Southern African Journal of Infectious Diseases, 2022)
Background: Candidemia is associated with high morbidity and mortality. The epidemiology of candidemia has changed globally over the past 20 years. South African surveillance demonstrated a shift in epidemiology from Candida albicans to non-albicans species including Candida parapsilosis and Candida auris. Hospital-level candidemia incidence from South Africa has not been reported previously.